Methane laser aspherical lens capable of preventing water vapor as well as preparation method and application of methane laser aspherical lens
By depositing alumina, magnesium fluoride, and silicon composite membrane layer on the surface of a methane laser aspherical lens on the surface, the problem of water condensation in the wet environment is solved, the light transmission and detection accuracy is improved, the service life is extended, and the service life is extended, and the service life is extended. Material cost.
Patent Information
- Application Number
- CN202411513073.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing methane laser aspherical lenses are prone to water vapor condensation in wet environments, resulting in reduced optical transparency and reduced detection accuracy. The existing waterproof mist film materials are not effective in environments without ultraviolet light exposure, and are costly and thermal. Poor stability.
The composite membrane composite from alumina, magnesium fluoride, and silicon oxide is used as a waterproof vapor membrane layer. The membrane layer is deposited on the surface of the non -spherical lens through the magnetic sputtering process to optimize the proportion of the composite material and the thickness of the membrane layer. In order to improve the thermal stability, light transmission and hydrophilicity of the membrane layer.
Achieve effectively prevent water vapor condensation in the wet environment, maintain laser transparency and detection accuracy, extend the service life, and reduce the cost of material.
Smart Images

Figure CN119375995A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a methane laser aspheric lens capable of preventing water vapor, and a preparation method and application thereof. Background Art
[0002] The laser methane sensor uses tunable laser gas absorption technology (TDLAS), which contains optical path structure, circuit design and algorithm compensation. It has high detection accuracy. In the detection of gas leakage, it has excellent gas selectivity, no oxygen dependence, and long life. It is gradually replacing traditional detection methods such as electrochemical catalytic combustion. However, in actual applications, the laser surface is fogged in the underground environment. The attachment of water vapor causes the light to hit the tiny water droplets for diffuse reflection, which reduces the transmittance of the laser output and causes the receiving intensity of the optical path detector to decrease. Experiments have shown that the light intensity has dropped by more than 1 / 2, resulting in a decrease in the detection accuracy of the methane sensor, causing sensor false alarms and monitoring failures, which will lead to major safety hazards in the long run. In particular, the laser package adopts the traditional TO56 or TO60 form. The light emitted by this package requires an aspheric lens to aggregate the divergent light beam into a light column. The aspheric lens fogs on the lens surface in the rainy environment of the plum rain season, causing the sensor light intensity to decay to the detection limit. The normal detection function will not be restored throughout the plum rain season. Therefore, it is very important to prepare an aspheric lens with water vapor condensation function.
[0003] At present, preparing a fog-proof film on the surface of an aspheric lens is a feasible solution for preventing water vapor condensation. However, the fog-proof film used in the prior art is mainly a TiO2 film coating. The film has good photocatalytic properties and exhibits high photocatalytic activity and super hydrophilicity and lipophilicity under ultraviolet light irradiation. However, the laser of this product is placed underground in a gas pipeline well, and the service environment is not exposed to sunlight ultraviolet rays, so this method is not suitable. In addition, some researchers have proposed a new type of optical coating material with anti-fog properties, including the following components: 0-50% nano-silicon dioxide, 0-10% zirconium dioxide, 0-5% zinc sulfide, 0-40% niobium pentoxide, and 0-20% yttrium oxide. However, the zirconium oxide used in the optical coating material will increase the hardness of the film, making it difficult for the film to be stably loaded on the surface of the aspheric lens. At the same time, the large-scale use of rare element materials such as zirconium dioxide, niobium pentoxide and yttrium oxide also makes its use cost very high, making it difficult to promote its use. In particular, it is difficult for the optical coating material to enhance the thermal stability of the film, making it easy for the film to fall off the mirror surface in high and low temperature environments, especially easier to fall off and break from the aspheric lens, making it difficult to be widely used to realize the anti-water vapor condensation function of the aspheric lens of the methane laser. In addition, some researchers have proposed a long-lasting anti-fog and easy-to-clean myopia glasses lens, in which a siliconized hardening film, a nano-aluminum oxide film, an anti-reflective coating, a nano-silicon dioxide film, a nano-anti-fog modified film and a protective film are sequentially arranged on the surface of the resin lens. Although the scratch resistance of immersion can be improved by setting the siliconized hardening film, the nano-anti-fog modified film and the protective film, it will also bring about the defect of excessive overall thickness of the lens, making it difficult to be applied to aspherical lenses. At the same time, a super-hydrophilic water film is formed between the resin lens and the dirt through the hydrophilic group of the nano-modified film. Although it can prevent the dirt from contacting the resin lens, it cannot effectively and timely remove the water vapor on the surface of the lens, resulting in condensation on the surface of the lens to form countless small water droplets, which will aggravate the occurrence of diffuse reflection and significantly reduce the transmittance of the laser emission, thereby causing the detection performance of the laser methane sensor to deteriorate, and even the presence of dirt will block the emission of the laser, causing the laser methane sensor to fail.
[0004] Therefore, obtaining a methane laser aspheric lens with good thermal stability, good light transmittance, good hydrophilicity and long service life is of great significance for achieving stable and accurate detection of laser methane sensors and promoting the widespread use of laser methane sensors. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a methane laser aspheric lens that is water vapor proof and has good thermal stability, good light transmittance, good hydrophilicity and long service life, as well as a preparation method and application thereof.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: A methane laser aspheric lens for preventing water vapor comprises an aspheric lens, the surface of which is provided with a water vapor-proof film layer; the water vapor-proof film layer is a composite film composed of aluminum oxide, magnesium fluoride and silicon dioxide.
[0007] The above-mentioned methane laser aspheric lens is further improved, wherein the mass percentage of aluminum oxide in the waterproof vapor film layer is 5% to 10%, the mass percentage of magnesium fluoride is 10% to 20%, and the mass percentage of silicon dioxide is 70% to 80%.
[0008] The above-mentioned methane laser aspheric lens is further improved in that the thickness of the waterproof vapor film layer is 200 nm to 230 nm.
[0009] The above-mentioned methane laser aspheric lens is further improved in that the diameter of the aspheric lens is 3 mm to 5 mm.
[0010] As a general technical concept, the present invention also provides a method for preparing a methane laser aspheric lens that prevents water vapor, comprising the following steps: S1. Provide aspheric lens; S2. A composite material of aluminum oxide, magnesium fluoride and silicon dioxide is used as a target material, and a magnetron sputtering process is used to deposit a water vapor-proof film layer on the surface of the aspherical lens.
[0011] The above preparation method is further improved, in step S2, the preparation method of the composite material of aluminum oxide, magnesium fluoride and silicon dioxide comprises the following steps: (1) mixing silicon dioxide powder, aluminum oxide powder and magnesium fluoride powder for pre-sintering; (2) placing the material obtained after pre-sintering in step (1) into a mold for secondary sintering to obtain a semi-finished product; (3) The semi-finished product obtained in step (2) is subjected to surface processing so that all surfaces of the semi-finished product remain flat, thereby obtaining a composite material of aluminum oxide, magnesium fluoride and silicon dioxide.
[0012] The above preparation method is further improved, in step (1), the mass ratio of the silicon dioxide powder, the aluminum oxide powder and the magnesium fluoride powder is 1-2:2-4:14-16; the silicon dioxide powder is prepared by the following method: mixing silicate with anhydrous ethanol, stirring, adding deionized water, adjusting the pH value of the solution, adding a surfactant, aging, and obtaining a gel; calcining the gel to obtain the silicon dioxide powder; the particle size of the silicon dioxide powder is nanometer-scale; the particle size of the aluminum oxide powder is 1μm-5μm; the particle size of the magnesium fluoride powder is 1μm-5μm; the pre-sintering is carried out at a temperature of 1000°C-1300°C; and the pre-sintering time is 8 hours-12 hours.
[0013] The above preparation method is further improved, in step (2), the secondary sintering is carried out under vacuum or inert atmosphere; the secondary sintering is carried out at a temperature of 1500°C; the pressure of the system is controlled to be maintained at 50MPa during the secondary sintering process; the composite material of aluminum oxide, magnesium fluoride and silicon dioxide is in the shape of a column with a diameter of 76.2mm and a height of 9mm.
[0014] The above preparation method is further improved, in step S1, the diameter of the aspheric lens is 3 mm to 5 mm.
[0015] The above preparation method is further improved. In step S2, the deposition process parameters of the waterproof film layer are: controlling the magnetron sputtering power to 150W, the Ar gas intake to 20sccm, the gas output to 20sccm, maintaining the sputtering vacuum to 0.4Pa, and the coating time to 2h to 2.5h.
[0016] The above preparation method is further improved, in step S2, the waterproof vapor film layer is a composite film composed of aluminum oxide, magnesium fluoride and silicon dioxide; the mass percentage of aluminum oxide in the waterproof vapor film layer is 5% to 10%, the mass percentage of magnesium fluoride is 10% to 20%, and the mass percentage of silicon dioxide is 70% to 80%; the thickness of the waterproof vapor film layer is 200 nm to 230 nm.
[0017] As a general technical concept, the present invention also provides a laser methane sensor, which includes the above-mentioned methane laser aspheric lens or the methane laser aspheric lens prepared by the above-mentioned preparation method.
[0018] Compared with the prior art, the advantages of the present invention are: (1) The present invention creatively provides a methane laser aspheric lens that prevents water vapor. By arranging a composite film composed of aluminum oxide, magnesium fluoride and silicon dioxide on the surface of the aspheric lens, a water vapor-proof film layer with good thermal stability, good light transmittance and good hydrophilicity can be formed on the surface of the aspheric lens. Specifically, under the action of aluminum oxide, the thermal stability adaptability between the water vapor-proof film layer and the aspheric lens can be enhanced, and the film layer can be effectively prevented from falling off and cracking under high and low temperature environments; under the action of magnesium fluoride, the refractive index of the film layer can also be reduced, thereby enhancing the light transmittance effect; under the action of silicon dioxide, the surface tension of the film layer can be enhanced, and the diffuse reflection of the laser can be reduced. The water contact angle can reach 13°, and experiments show that when the water contact angle is ≤25°, the film layer has anti-fogging performance. The methane laser aspheric lens of the present invention has a composite film composed of aluminum oxide, magnesium fluoride and silicon dioxide arranged on the surface of the aspheric lens, has the advantages of good thermal stability, good light transmittance, good hydrophilicity, long service life, etc., can effectively prevent the methane laser aspheric lens from appearing water mist, and the anti-fog duration is long, can be used to construct a laser methane sensor, can realize stable and accurate detection of the laser methane sensor, has high use value, and has good application prospects.
[0019] (2) In the methane laser aspheric lens of the present invention, by optimizing the mass percentage of aluminum oxide in the waterproof film layer to 5% to 10%, the mass percentage of magnesium fluoride to 10% to 20%, and the mass percentage of silicon dioxide to 70% to 80%, the wear resistance and light transmittance of the film layer can be significantly improved, and at the same time, the hydrophilicity of the film layer can be greatly improved, so that the laser can smoothly penetrate the aspheric lens without refraction.
[0020] (3) In the methane laser aspheric lens of the present invention, by optimizing the thickness of the water vapor-proof film layer to 200 nm to 230 nm, the obvious refraction of the laser can be significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0022] Figure 1 Schematic diagram of the structure of the aspheric lens of the methane laser for preventing water vapor in Example 1 of the present invention.
[0023] Figure 2 Schematic diagram of the water contact angle on the surface of the aspheric lens of the methane laser for preventing water vapor in Example 1 of the present invention.
[0024] Legend: 1. Waterproof vapor film layer; 2. Aspherical lens. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0026] Embodiment 1: like Figure 1 As shown, a methane laser aspheric lens for preventing water vapor comprises an aspheric lens 2, on the surface of which a water vapor-proof film layer 1 is provided, wherein the water vapor-proof film layer 1 is a composite film composed of aluminum oxide, magnesium fluoride and silicon dioxide.
[0027] In this embodiment, the mass percentage of aluminum oxide in the waterproof vapor-proof film layer is 7%, the mass percentage of magnesium fluoride is 18%, and the mass percentage of silicon dioxide is 75%.
[0028] In this embodiment, the thickness of the waterproof vapor-proof film layer is 220 nm.
[0029] In this embodiment, the diameter of the aspheric lens is 3 mm.
[0030] A method for preparing the above-mentioned methane laser aspheric lens that prevents water vapor comprises the following steps: S1. Provide an aspheric lens, wherein the diameter of the aspheric lens is 3 mm.
[0031] S2. A composite material of aluminum oxide, magnesium fluoride and silicon dioxide was used as a target material, and a magnetron sputtering process was adopted to deposit a water-proof vapor film layer on the surface of the aspheric lens. The deposition process parameters of the water-proof vapor film layer were as follows: the magnetron sputtering power was controlled to be 150 W, the Ar gas intake volume was 20 sccm, the gas output volume was 20 sccm, the sputtering vacuum was maintained at 0.4 Pa, and the coating time was 2 h.
[0032] In this embodiment, the preparation method of the composite material of aluminum oxide, magnesium fluoride and silicon dioxide comprises the following steps: (1) Silica powder, alumina powder and magnesium fluoride powder were mixed in a mass ratio of 7:18:85, and the mixture was heated to 1200° C. for pre-sintering for 10 hours.
[0033] (2) The material obtained after pre-sintering in step (1) is placed in a graphite mold, heated to 1500° C. and maintained at a pressure of 50 MPa under an inert atmosphere, and subjected to secondary sintering to obtain a highly dense sputtering target semi-finished product.
[0034] (3) The high-density sputtering target semi-finished product obtained in step (2) is surface-processed to make all surfaces of the semi-finished product flat, thereby obtaining a composite material of aluminum oxide, magnesium fluoride and silicon dioxide, wherein the composite material of aluminum oxide, magnesium fluoride and silicon dioxide is in a columnar shape with a diameter of 76.2 mm and a height of 9 mm (including a 3 mm copper backing plate).
[0035] In this embodiment, the silicon dioxide powder is prepared by the following method: mixing silicate with anhydrous ethanol, stirring, adding deionized water, adjusting the pH value of the solution, adding a surfactant, aging, and obtaining a gel; and calcining the gel to obtain the silicon dioxide powder.
[0036] In this embodiment, the particle size of the silicon dioxide powder is nanometer level.
[0037] In this embodiment, the particle size of the aluminum oxide powder is 1 μm to 5 μm.
[0038] In this embodiment, the particle size of the magnesium fluoride powder is 1 μm to 5 μm.
[0039] After testing, the water contact angle of the water vapor-proof methane laser aspheric lens prepared in the above embodiment can reach 13°. Figure 2 shown.
[0040] A laser methane sensor comprises the methane laser aspheric lens prepared above.
[0041] In this embodiment, water vapor-proof film layers with different ratios of aluminum oxide, magnesium fluoride and silicon dioxide were prepared, with other conditions being the same. Their water contact angles are shown in Table 1.
[0042] Table 1 Water contact angles of water vapor barrier layers with different ratios of aluminum oxide, magnesium fluoride and silicon dioxide
[0043] It can be seen from Table 1 that under the conditions of different proportions of the three components of the composite film layer, when the mass fraction of aluminum oxide is 7%, magnesium fluoride is 18%, and silicon dioxide is 75%, the water contact angle of the composite film layer is the minimum of 13°, which is the optimal ratio.
[0044] In this embodiment, waterproof vapor film layers with different thicknesses were also prepared. Other conditions were the same as those in Example 1. Their water contact angles are shown in Table 2.
[0045] Table 2 Water contact angle of waterproof vapor film with different thicknesses
[0046] It can be seen from Table 2 that when the thickness of the waterproof vapor film layer is 200 nm to 230 nm, it has good hydrophilicity. In particular, when the thickness of the film layer is 220 nm, the water contact angle is the smallest, which is the optimal thickness of the film layer. At the same time, when the thickness of the waterproof vapor film layer is 200 nm to 230 nm, it can significantly reduce the obvious refraction of the laser.
[0047] It can be seen from the above results that, compared with conventional aspheric lenses, the methane laser aspheric lens of the present invention has a composite film composed of aluminum oxide, magnesium fluoride and silicon dioxide arranged on the surface of the aspheric lens, which has the advantages of good thermal stability, good light transmittance, good hydrophilicity, long service life, etc., can effectively prevent the methane laser aspheric lens from appearing water mist, and the anti-fog duration is long, can be used to construct a laser methane sensor, can realize stable and accurate detection of the laser methane sensor, has high use value, and has good application prospects.
[0048] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A methane laser aspheric lens to prevent water vapor, characterized in that: It comprises an aspherical lens, the surface of which is provided with a water-proof vapor film layer; the water-proof vapor film layer is a composite film composed of aluminum oxide, magnesium fluoride and silicon dioxide.
2. The methane laser aspheric lens according to claim 1, characterized in that: The mass percentage of aluminum oxide in the waterproof vapor-proof membrane layer is 5% to 10%, the mass percentage of magnesium fluoride is 10% to 20%, and the mass percentage of silicon dioxide is 70% to 80%.
3. The methane laser aspheric lens according to claim 1 or 2, characterized in that: The thickness of the waterproof vapor-proof film layer is 200 nm to 230 nm.
4. The methane laser aspheric lens according to claim 3, characterized in that: The diameter of the aspherical lens is 3 mm to 5 mm.
5. A method for preparing a methane laser aspheric lens that prevents water vapor, characterized in that: The following steps are involved: S1. Provide aspheric lens; S2. A composite material of aluminum oxide, magnesium fluoride and silicon dioxide is used as a target material, and a magnetron sputtering process is used to deposit a water vapor-proof film layer on the surface of the aspherical lens.
6. The preparation method according to claim 5, characterized in that: In step S2, the method for preparing the composite material of aluminum oxide, magnesium fluoride and silicon dioxide comprises the following steps: (1) mixing silicon dioxide powder, aluminum oxide powder and magnesium fluoride powder for pre-sintering; (2) placing the material obtained after pre-sintering in step (1) into a mold for secondary sintering to obtain a semi-finished product; (3) The semi-finished product obtained in step (2) is subjected to surface processing so that all surfaces of the semi-finished product remain flat, thereby obtaining a composite material of aluminum oxide, magnesium fluoride and silicon dioxide.
7. The preparation method according to claim 6, characterized in that: In step (1), the mass ratio of the silicon dioxide powder, the aluminum oxide powder and the magnesium fluoride powder is 1-2:2-4:14-16; the silicon dioxide powder is prepared by the following method: mixing silicate with anhydrous ethanol, stirring, adding deionized water, adjusting the pH value of the solution, adding a surfactant, aging, and obtaining a gel; calcining the gel to obtain the silicon dioxide powder; the particle size of the silicon dioxide powder is nanometer-scale; the particle size of the aluminum oxide powder is 1 μm-5 μm; the particle size of the magnesium fluoride powder is 1 μm-5 μm; the pre-sintering is carried out at a temperature of 1000° C. to 1300° C.; the pre-sintering time is 8 hours to 12 hours; In step (2), the secondary sintering is carried out in a vacuum or inert atmosphere; the secondary sintering is carried out at a temperature of 1500° C.; the pressure of the control system is maintained at 50 MPa during the secondary sintering process; the composite material of aluminum oxide, magnesium fluoride and silicon dioxide is in a columnar shape with a diameter of 76.2 mm and a height of 9 mm.
8. The preparation method according to any one of claims 5 to 7, characterized in that In step S1, the diameter of the aspheric lens is 3 mm to 5 mm; In step S2, the deposition process parameters of the waterproof vapor film layer are: controlling the magnetron sputtering power to 150W, the Ar gas intake to 20sccm, the gas output to 20sccm, maintaining the sputtering vacuum degree to 0.4Pa, and the coating time to 2h to 2.5h.
9. The preparation method according to claim 8, characterized in that In step S2, the waterproof vapor film layer is a composite film composed of aluminum oxide, magnesium fluoride and silicon dioxide; the mass percentage of aluminum oxide in the waterproof vapor film layer is 5% to 10%, the mass percentage of magnesium fluoride is 10% to 20%, and the mass percentage of silicon dioxide is 70% to 80%; the thickness of the waterproof vapor film layer is 200 nm to 230 nm.
10. A laser methane sensor, characterized in that: The laser methane sensor comprises the methane laser aspheric lens according to any one of claims 1 to 4 or the methane laser aspheric lens prepared by the preparation method according to any one of claims 5 to 9.
Citation Information
Patent Citations
Method for preparing nanometer silicon dioxide
CN101125655A
Moisture barrier film, preparation method thereof and display containing the same
CN105405986A
Monodisperse submicron grade silica microsphere and preparation method thereof
CN106745009A
High-brightness PET reflective film
CN111308594A
Prepn of silicon dioxide powder with controllable nanon size
CN1117022A